(untitled) (Journal of Science and Technology, 2016)
The purpose 4 this artic le. is to highlight on the traditional gained wooden stool at a curliest art work. and also, as the must important single artefact in the traditional Ghanaian Chief’s or King’s artistic paraphernalia. As an artwork. its design elements and production processes have been discussed. The selection of appropriate woods and design motifs for production and their symbolism have also been considered. the various type of stools available and their significance in the socio-political religious milieu of Southern Ghanaians. have been given prominence